Effects of Thyme (Thymus vulgaris) Essential Oil on Bacterial Growth and Expression of Some Virulence Genes in Salmonella enterica Serovar Enteritidis - Mohammad Hassanzadeh; Sara Mirzaie; Faezeh Rahimi Pirmahalle; Ramak Yahyaraeyat; Jamshid Razmyar (Veterinary Medicine and Science)
ABSTRACT Background The investigation on natural antimicrobial compounds against zoonotic pathogens has gained more attention due to the public health concerns regarding the emergence of antimicrobial resistance. Objectives The current study aimed to assess the effects of thyme essential oil at sub‐minimal inhibitory concentrations (sub‐MICs) on bacterial growth and expression of some virulence genes in Salmonella enteritidis. Methods The bacterial growth rate and the expression of four virulence genes in S. enteritidis during 18–72 h of exposure to the essential oil at 25%–75% MIC were evaluated via colony counting and real‐time polymerase chain reaction (PCR), respectively. Results Sub‐inhibitory concentrations of thyme essential oil significantly reduced the growth rate compared to the control. Expression of all tested virulence genes was also reduced by the essential oil in a significant dose‐ and time‐dependent manner. As an example, decreased down‐regulation of hilA, spv, sefA and invA as 1.7‐, 4.14‐, 2.92‐ and 1.04‐fold in 25% MIC and 6.42‐, 7.81‐, 4.4‐ and 3.75‐fold in 75% MIC was observed, respectively, after 24 h of incubation. Likewise, levels of transcription for hilA, spv, sefA and invA were reduced 4.75‐, 6.95‐, 3.75‐ and 2.98‐fold after 18 h and 9.54‐, 8.81‐, 5.65‐ and 4.77‐fold, respectively, after 72 h in 75% MIC compared to the control. Conclusions According to our data, aside from the growth inhibitory effect of thyme essential oil, the results of current study highlight the potential of thyme for reducing the transcriptional level of virulence genes and therefore the pathogenicity of S. enteritidis.